Impact of Novel Coronavirus (COVID-19) on Aspects of Personal and Professional Life - Rana, Khurram Shahnawaz; Abid, Dr. Ghulam; Nisar, Asma; Nawaz, Muhammad (The journal of contemporary issues in business and government, 2021)
Novel coronavirus (COVID-19) is officially a pandemic now. With around 30-40 % workforce working from home and around 30% unemployment expected, so far by analysts, it is becoming very important to understand the personal and professional impact that this pandemic is having on professionals.In the last weeks, alone many ICT companies have downsized, reduced pay, or stopped benefits in order to handle the economic strain caused by the pandemic while factories and manufacturing concerns have come to a halt. On a personal level, staying at home, isolation, unemployment, financial strain occurs that can cause numerous behavioral concerns. The aim of this paper is to do an exploratory study with a mix of auto ethnographic view and identify professional and personal effects both positive and negative due to the COVID-19 pandemic and repercussions for professionals. As COVID-19 is an ongoing pandemic, thereby to the best of our knowledge, no study has been conducted which explain the impact of COVID-19 on personal and professional lives with the qualitative context we adopted.